2020
DOI: 10.1111/ijac.13582
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding B2O3 on microwave dielectric properties of 0.9625MgTiO3‐0.0375(Ca0.5Sr0.5)TiO3 composite ceramics

Abstract: A series of 0.9625MgTiO 3-0.0375(Ca 0.5 Sr 0.5)TiO 3 composite ceramics added with different amounts of B 2 O 3 (1-5 wt%) were prepared via the solid state sintering method using the pre-synthesized raw MgTiO 3 and (Ca 0.5 Sr 0.5)TiO 3 powders by molten-salt reaction. The sintering temperature of 0.9625MgTiO 3-0.0375(Ca 0.5 Sr 0.5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Peng et al. found that the 0.9625MgTiO 3 ‐0.0375Ca 0.5 Sr 0.5 TiO 3 ceramic with 2 wt % B 2 O 3 exhibited great microwave dielectric properties ( ϵ r =18.9, Q×f =57,000 GHz and τ f =−1.2 ppm/°C) after sintered at 1175 °C [8] . Besides, the sintering temperature of the 0.95MgTiO 3 ‐0.05CaTiO 3 ceramic could be effectively lowered to 1050 °C with 15wt % 60ZnO‐30B 2 O 3 ‐10SiO 2 , however, the dielectric properties have sharply deteriorated to Q× f =29,000 GHz, and τ f =−10.2 ppm/°C [9] …”
Section: Introductionmentioning
confidence: 99%
“…Peng et al. found that the 0.9625MgTiO 3 ‐0.0375Ca 0.5 Sr 0.5 TiO 3 ceramic with 2 wt % B 2 O 3 exhibited great microwave dielectric properties ( ϵ r =18.9, Q×f =57,000 GHz and τ f =−1.2 ppm/°C) after sintered at 1175 °C [8] . Besides, the sintering temperature of the 0.95MgTiO 3 ‐0.05CaTiO 3 ceramic could be effectively lowered to 1050 °C with 15wt % 60ZnO‐30B 2 O 3 ‐10SiO 2 , however, the dielectric properties have sharply deteriorated to Q× f =29,000 GHz, and τ f =−10.2 ppm/°C [9] …”
Section: Introductionmentioning
confidence: 99%
“…Dielectric materials having approximately zero τ f value can be produced by the most widely used methods i.e., by mixing two or more materials with opposite τ f values and forming mixed phases and solid solution. [12][13][14] In the literature, the perovskite-structured CaTiO 3 (ε r = 170, τ f = 800 ppm °C−1 , Q × f = 3600 GHz) are typically added into microwave dielectric ceramics because of their high positive τ f value. [7][8][9][10][11] Therefore, by doping a smaller amount of secondary CaTiO 3 phase, such a combination has been predicted to produce a MgTiO 3 -based composite with approximately zero τ f , high Q × f, and even high ε r value.…”
mentioning
confidence: 99%